2015
DOI: 10.1128/jvi.01976-15
|View full text |Cite
|
Sign up to set email alerts
|

Mimivirus Fibrils Are Important for Viral Attachment to the Microbial World by a Diverse Glycoside Interaction Repertoire

Abstract: Acanthamoeba polyphaga mimivirus (APMV) is a giant virus from the Mimiviridae family. It has many unusual features, such as a pseudoicosahedral capsid that presents a starfish shape in one of its vertices, through which the ϳ1.2-Mb double-stranded DNA is released. It also has a dense glycoprotein fibril layer covering the capsid that has not yet been functionally characterized. Here, we verified that although these structures are not essential for viral replication, they are truly necessary for viral adhesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 29 publications
1
56
0
Order By: Relevance
“…Using several different approaches, we have demonstrated that MsV either can interact with the cell surface and enter through endocytosis or can be found inside giant vesicles that stimulate the phagocytosis mechanism. Finally, the discovery of giant viruses not only has brought to light their genomic complexity, with hundreds of new genes/proteins that are able to perform activities never before attributable to a virus, but also allowed us a glimpse into a microcosm of ecological interactions, where viruses are able, for example, to actively seek new hosts and habitats by adsorbing into other, more complex life forms, such as fungi and arthropods (14). Here, we have identified yet another possible ecological strategy for the release of a giant virus from its last host in vesicles that have the potential to boost its entry into another host, as well as to help it endure in the environment during an "interhost" period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using several different approaches, we have demonstrated that MsV either can interact with the cell surface and enter through endocytosis or can be found inside giant vesicles that stimulate the phagocytosis mechanism. Finally, the discovery of giant viruses not only has brought to light their genomic complexity, with hundreds of new genes/proteins that are able to perform activities never before attributable to a virus, but also allowed us a glimpse into a microcosm of ecological interactions, where viruses are able, for example, to actively seek new hosts and habitats by adsorbing into other, more complex life forms, such as fungi and arthropods (14). Here, we have identified yet another possible ecological strategy for the release of a giant virus from its last host in vesicles that have the potential to boost its entry into another host, as well as to help it endure in the environment during an "interhost" period.…”
Section: Discussionmentioning
confidence: 99%
“…The pellet containing vesicles was collected and the supernatant containing only naked particles was discarded. After this purification, the samples were prepared for analysis by scanning electron microscopy (SEM), as previously described (14). Furthermore, we also evaluated if these vesicles could be phagocytosed by amoebas.…”
Section: Methodsmentioning
confidence: 99%
“…Whether the unusual sugar 4‐amino‐4,6‐dideoxy‐ d ‐glucose is important for infection is presently unclear. What is known, however, is that the heavily glycosylated fibril layer of the virus is required for adhesion to the host organism . It is also not known whether giant viruses are capable of widespread human infections.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of morphology, the APMV capsid displays pseudoicosahedral symmetry and is composed of proteins adopting the “double jelly roll fold.” Surrounding the capsid is a densely packed arrangement of highly glycosylated protein fibers that play a role in viral adhesion to its natural host, the amoeba . With respect to the glycan composition of the viral fibers, it has been shown that the unusual sugar 4‐amino‐4,6‐dideoxy‐ d ‐glucose is associated with these fibers .…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that these fibers work in tandem with the large size of the viruses to facilitate phagocytosis, as they appear to have a similar composition to peptidoglycan and thus help mimic a bacterium (indeed, the name Mimivirus comes from “ Mimicking Microbe ” [29]). Additionally, the fibrous glycoproteins enable viral adsorption to diverse organisms ranging from bacteria and fungi to arthropods [30], implying a potential for both environmental dispersion and an incidental infection strategy in amoeba. Phycodnaviridae may also use unique structures to gain access to their host, though their mode of entry is typically by adsorption/injection, as opposed to phagocytosis.…”
Section: Introduction: Defining Giant Virusesmentioning
confidence: 99%